Study of tribenzo[b,d,f]azepine as donor in D–A photocatalysts - Medrano-Uribe, Katy; Humbrías-Martín, Jorge; Dell’Amico, Luca (Beilstein Journal of Organic Chemistry, 2025)
Since the discovery of donor–acceptor (D–A) type molecules in the field of materials science, they have found great applicability in the field of photocatalysis. Most of these compounds are based on complex D–A–D structures or multi-D–A systems, such as 4CzIPN. Whereas these systems have been widely studied and applied as photocatalysts, simpler D–A structures remain less explored. Nevertheless, the simplicity of D–A structures makes them the ideal structures to further understand the structure–property relationship of D–A molecules for optimizing their photocatalytic performance by simpler modification of the different D–A subunits. In particular, D–A structures featuring sulfur-based acceptors and nitrogen donors have gained increasing attention for their use as photoredox catalysts. This study introduces a new family of D–A molecules by exploring various sulfur-based acceptors and nitrogen donors, including a novel tribenzo[b,d,f]azepine (TBA) unit and 5H-dibenz[b,f]azepine (IMD). Our findings demonstrate that these simple D–A structures exhibit promising photocatalytic properties, comparable to those of more complex D–A–D systems.
Keywords: donor–acceptor system; photocatalyst design; photoredox catalysis; organic photocatalyst